Drive beam sources and longitudinal shaping techniques for beam driven accelerators. (1st May 2022) - Lemery, F.; Andonian, G.; Doebert, S.; Ha, G.; Lu, X.; Power, J.; Wisniewski, E.
Abstract: Linear colliders are an attractive platform to explore high-precision physics of newly discovered particles. The recent significant progress in advanced accelerator technologies has motivated their applications to colliders which has been discussed in the alegro workshop. In this paper we discuss structure wakefield acceleration, namely collinear wakefield acceleration and two-beam acceleration. We especially discuss available drive and witness beam sources based on L and S-band radiofrequency technology, and also summarize available and forthcoming longitudinal shaping techniques to improve the overall acceleration efficiency via the transformer ratio.